Pelaksanaan user education (pendidikan pemakai) di Perpustakaan Universitas Mercu Buana Yogyakarta - Wildan Novia Rosydiana; Labibah Labibah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
User education activities in college libraries are activities provide information on utilizing library services properly and correctly. UMBY Library organizes this activity for new and old students who have not participated and makes this activity routine agenda is carried out at the beginning of each new school year. This study aims to determine the implementation and role of user education in the utilization of services the UMBY library. The research method used is qualitative research by taking 11 respondents consisting of one Head of Library and three Librarians in the technical implementation section as well as three students of class 2021 and four students of class 2022. The data collection methods used are observation, interview, and documentation. The results of this study indicate that the implementation of user education in the UMBY library in the 2022/2023 academic year was carried out with adjustments to the covid-19 health protocol because it was carried out during a pandemic, then the implementation of user education was only carried out with two models, namely library orientation and library teaching using the lecture method. The role of user education seen from the utilization of available services, searching for information, and the ability to use services.